The dynamic immune response of the liver and spleen in leopard coral grouper (Plectropomus leopardus) to Vibrio harveyi infection based on transcriptome analysis - Liu, Yang; Lu, Sheng; Guo, Mengqi; Wang, Ziyuan; Hu, Bowen; Zhou, Bo; Chen, Songlin (Frontiers in Immunology, 2024)
Leopard coral grouper (Plectropomus leopardus) is one of the most important cultured fish in Pacific and Indian oceans. Vibrio harveyi is a serious pathogen causing serious skin ulceration and high mortality in P. leopardus. To gain more insight into the tissue-specific and dynamic immune regulation process of P. leopardus in response to V. harveyi infection, RNA-seq was used to examine the transcriptome profiles in spleen and liver at 0, 6, 12, 24, 48 and 72 h post-infection.The up-regulated differentially expressed genes (DEGs) were predominantly involved in the immune response in the spleen and liver at the early infection stage (6-12 h), and down-regulated DEGs were mainly involved in metabolic processes in the liver at the early and middle infection stage (6-48 h). Moreover, an overview of the immune response of P. leopardus against V. harveyi was exhibited including innate and adaptive immune related pathways. Afterwards, the results of WGCNA analysis in the spleen indicated that TAP2, IRF1, SOCS1 and CFLAR were the hub genes closely involved in immune regulation in the gene co-expression network. This study provides a global picture of V. harveyi-induced gene expression profiles of P. leopardus at the transcriptome level and uncovers a set of key immune pathways and genes closely linked to V. harveyi infection, which will lay a foundation for further study the immune regulation of bacterial diseases in P. leopardus.